P53 in the impaired lungs (2020)
Our laboratory is focused on investigating the supportive role of P53 towards the maintenance of lung homeostasis. Acute lung injury, acute respiratory distress syndrome, chronic obstructive pulmonary disease, pulmonary fibrosis, bronchial asthma, pulmonary arterial hypertension, pneumonia and tuberculosis are respiratory pathologies, associated with dysfunctions of this endothelium defender (P53). Herein we review the evolving role of P53 towards the aforementioned inflammatory disorders, to potentially reveal new therapeutic possibilities in pulmonary disease.